Identification of divergent PTPN11 mutations in canine histiocytic sarcomas reveals evidence of an independent clonal origin - Stéphanie Mottier; Armel Houel; Solveig Bouchard; Charline Bianchi; Louis Le Nezet; Richard Guyon; Stéphane Dreano; Thomas Derrien; Jerôme Abadie; Catherine André; Benoît Hédan (PLoS ONE, 2026)
Background Histiocytic sarcoma (HS) is a rare but highly aggressive neoplasm in humans, with limited knowledge on indicators markers and no standardized treatment. Dogs naturally develop HS, offering a powerful comparative model. Activating mutations in PTPN11 , affecting two recurrent hotspots (E76 and G503), are the most frequent drivers of canine HS and are strongly associated with the disseminated form (DHS). While DHS is typically considered metastatic, we hypothesize that multiple independent tumor clones may arise within the same individual. Methods We investigated clonal heterogeneity in 38 dogs affected with DHS presenting tumors in both abdominal and thoracic organs. PTPN11 hotspot mutations were analyzed by high-sensitivity droplet digital PCR (ddPCR) to detect low-abundance variants. The frequency of divergent mutations between tumor sites was used to infer the proportion of cases arising from independent clonal origins. Results Divergent PTPN11 mutations were directly observed in 3 of 28 dogs with PTPN11 -mutated tumor pairs. After correcting for the limited detectability inherent to hotspot-based analysis, we estimated that, in this cohort, up to 24–45% of DHS cases may harbor clonally independent PTPN11 mutations in distinct tumors. In addition, analysis of somatic mutations and copy number variants by Next Generation Sequencing (NGS) in two cell lines derived from the same patient confirmed the independent origin of the clones. Conclusions Our findings suggest that a significant numbers of dogs with DHS develop several genetically distinct HS lesions either simultaneously or within a short time interval. This need to be confirmed in larger cohorts but this clonal diversity challenges the assumption that DHS is predominantly metastatic and has major implications for prognosis, therapeutic strategies, and the use of canine HS as a comparative model for human disease. Further exploration of clonal evolution in HS is warranted to improve treatment approaches in both species.